The Presence of IL-17A and T Helper 17 Cells in Experimental Mouse Brain Tumors and Human Glioma - Wainwright, Derek A. (Public Library of Science, 2010)
BACKGROUND: Recently, CD4(+)IL-17A(+) T helper 17 (Th17) cells were identified and reported in several diseased states, including autoimmunity, infection and various peripheral nervous system tumors. However, the presence of Th17 in glia-derived tumors of the central nervous system has not been studied. METHODOLOGY/PRINCIPAL FINDINGS: In this report, we demonstrate that mRNA expression for the Th17 cell cytokine IL-17A, as well as Th17 cells, are present in human glioma. The mRNA expression for IL-17A in glioma was recapitulated in an immunocompetent mouse model of malignant glioma. Furthermore, the presence of Th17 cells was confirmed in both human and mouse glioma. Interestingly, some Th17 cells present in mouse glioma co-expressed the Th1 and Th2 lineage markers, IFN-γ and IL-4, respectively, but predominantly co-expressed the Treg lineage marker FoxP3. CONCLUSIONS: These data confirm the presence of Th17 cells in glia-derived CNS tumors and provide the rationale for further investigation into the role of Th17 cells in malignant glioma.